SIGNIFICANCE OF PREOPERATIVE EXTERNAL LIMITING MEMBRANE HEIGHT ON VISUAL PROGNOSIS IN PATIENTS UNDERGOING MACULAR HOLE SURGERY. Issue 7 (July 2019) - Geenen, Caspar; Murphy, Declan C.; Sandinha, Maria T.; Rees, Jon; Steel, David H. W.
Abstract : Purpose: To investigate the association between the vertical elevation of the external limiting membrane (ELM) and visual outcome in patients undergoing surgery for idiopathic full-thickness macular hole. Methods: Retrospective observational study of a consecutive cohort of patients undergoing vitrectomy to treat macular hole. The greatest vertical height of the central ELM above the retinal pigment epithelium (ELM height) was measured on spectral domain optical coherence tomography preoperatively. The relationship of ELM height to other preoperative and postoperative variables, including macular hole width and height, and visual acuity was analyzed. Results: Data from 91 eyes of 91 patients who had undergone successful hole closure were included. The mean ELM height was 220 μ m (range 100–394). There were significant correlations between the ELM height and the diameter of the hole, hole height, and worsening preoperative visual acuity. For holes less than 400 μ m in width, better postoperative visual acuity was significantly predicted by a lower ELM height. Conclusion: The ELM height varies widely in idiopathic macular hole. It is higher in eyes where the hole is wider and also when the hole itself is higher. For holes of less than 400 μ m in width, a lower ELM height is a strong independent predictor of a good postoperative outcome. Abstract : The vertical height of the external limiting membrane above the retinal pigment epithelium was studied in a cohort of patients with idiopathic macular holes and found to vary widely. Its extent correlated with hole width and height. For small- and medium-sized holes, lower external limiting membrane height was a strong independent predictor of good postoperative outcome.